Development of a standardized methodology for selecting candidate DNA barcodes of Trillium govanianum to combat biodiversity crime and environmental exploitation - Tina Sharma; Mukesh Kumar Thakar (Forensic Science International: Animals and Environments, 2024)
This study introduces an innovative method using DNA barcodes to accurately identify species, addressing the critical issue of trafficking invaluable medicinal plants like Trillium govanianum. The success rate in amplification and sequencing of barcoding regions was an impressive 100%. The Internal Transcribed Spacer (ITS) region proved most effective in distinguishing closely related Trillium species. By testing herbal products from markets, the study revealed extensive illegal trade, with 50% confirmed as Trillium govanianum and 30% adulterated with Dioscorea villosa. This research contributes new DNA sequences to identification databases, enhancing protocols. Genetic variations within Trillium govanianum were narrower than to the nearest non-conspecific neighbor in barcoding regions (matK: 0.006, rbcL: 0.003, ITS: 0.043). Combining coding and non-coding regions (matK + ITS) achieved 100% species discrimination. Market samples showed 30% product substitution, with varying success rates for amplification (rbcL: 70%, matK: 60%, ITS: 40%, improved with ITS2 primers). Half the sequences were Trillium govanianum, 30% were Dioscorea villosa, revealing covert substitution. ITS and matK sequences were effective, with a genetic distance gap, while rbcL had limited divergence (0.003), making it less suitable for accurate identification compared to matK and ITS.